Steamboats PROSPECTOR (foreground) and BONANZA KING on the Yukon River at Whitehorse, Yukon Territory, 1901. - University of Washington Libraries. Special Collections Division
PH Coll 246.185 [Meed journal: "Steamer "Prospector" as a single decker taken immediately after being launched by Richard Stephens, boat builder who is standing between the ladder and the pilot house. White Horse. 1901."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number